2016
DOI: 10.1016/j.neubiorev.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The genesis of errors in drawing

Abstract: The difficulty adults find in drawing objects or scenes from real life is puzzling, assuming that there are few gross individual differences in the phenomenology of visual scenes and in fine motor control in the neurologically healthy population. A review of research concerning the perceptual, motoric and memorial correlates of drawing ability was conducted in order to understand why most adults err when trying to produce faithful representations of objects and scenes. The findings reveal that accurate percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…On the other hand, the visual perception of artists may differ from that of average observers. For example, it has been observed that skilled artists may differ in aspects of visual cognition (Chamberlain & Wagemans, 2015, 2016; Kozbelt, 2001; Perdreau & Cavanagh, 2013a, 2014, but see Perdreau & Cavanagh, 2013b). Chamberlain, McManus, Brunswick, Rankin, and Riley (2015) found that in a large population of student artists greater drawing ability was correlated with higher ROCF copy scores, and Gallagher and Burke (2007) found differences in raw ROCF scores based on factors such as IQ and gender.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the visual perception of artists may differ from that of average observers. For example, it has been observed that skilled artists may differ in aspects of visual cognition (Chamberlain & Wagemans, 2015, 2016; Kozbelt, 2001; Perdreau & Cavanagh, 2013a, 2014, but see Perdreau & Cavanagh, 2013b). Chamberlain, McManus, Brunswick, Rankin, and Riley (2015) found that in a large population of student artists greater drawing ability was correlated with higher ROCF copy scores, and Gallagher and Burke (2007) found differences in raw ROCF scores based on factors such as IQ and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Research on artist versus non-EXPERTS IN VISUAL COGNITION 7 artist differences in perception has gathered momentum in the last decade (Chamberlain & Wagemans, 2016;Kozbelt & Ostrofsky, in press). Some key findings, such as an association between drawing skill and local visual processing, have replicated repeatedly (Chamberlain et al, 2013;Chamberlain & Wagemans, 2015;Drake & Winner, 2011).…”
Section: Artists and Perception: Where Things Standmentioning
confidence: 99%
“…Although no direct assessment was made of the students' observational abilities, this course integrated observational theory into the sessions and therefore an improved ability to interpret visual information might be an indirectly acquired skill. Certainly, flaws in visual perception are commonly identified as the origin of drawing errors (Chamberlain & Wagemans, 2016) and it seems reasonable to infer that an improved facility to draw would be commensurate with improved observation. Examining if better drawing is a product of better observation would be an interesting area for future studies.…”
Section: Improvement In Drawing Skillsmentioning
confidence: 99%